Study of IL-33 During Pregnancy Period in Women Infected With T.Gondii and Healthy Pregnant Women: Studi IL-33 Selama Masa Kehamilan pada Wanita yang Terinfeksi T.Gondii dan Wanita Hamil yang Sehat - Shaker , Maha Mahmoud (Indonesian Journal on Health Science and Medicine, 2024)
Introduction, Toxoplasmosis disease is a parasitic infection that affects women, especially during pregnancy, due to low immunity, so women are vulnerable to infection, including infection with this parasite. The brain and the immune system are the two major adaptive systems in the body, and one regulates the other. There are indications that immune factors may be involved in the pathogenesis of neurodevelopmental disorders. Material and method A total of 90 samples were collected from women infected with toxoplasmosis during pregnancy and divided into two groups according to the questionnaire that was distributed to them. Results The results showed that there was an increase in the level of cytokine (interleukin 33) in pregnant women with toxoplasmosis as compared with the control group. Conclusion and recommendation The rise in the level of this cytokine may be due to its being an immune factor that mediates the inflammatory process that may occur as a result of infection with this parasite Highlights: Toxoplasmosis affects pregnant women due to weakened immunity. Increased interleukin-33 levels observed in infected pregnant women. Elevated cytokines mediate inflammation linked to toxoplasmosis infection. Keywords: Toxoplasmosis, Pregnancy, Cytokines, Interleukin-33, Immune Response